Permanent Campaigning: A Meta-Analysis and Framework for Measurement. Issue 1 (2nd January 2023) - Joathan, Ícaro; Lilleker, Darren G.
Abstract: Permanent campaigning emerged as a concept in the 1970s in studies of US politics but is now recognized as a universal phenomenon. Despite its long history, there has been no attempt to build a holistic picture of the elements that constitute a permanent campaign. Generally, researchers focus on tactical elements, situating their use within an overall strategy, but there is a lack of a broader methodological framework for holistically measuring adherence to the permanent campaigning. This article presents results of a meta-analysis of relevant research to provide a framework to understand how permanent campaigning is practiced. Our study showed there were three reasonably discrete forms of campaigning activities that had been identified: those in which permanent campaign strategies are related to capacity building and strategy; a second, in which permanent campaigning relates to paid and owned media; and a third in which earned media is the main focus. In mapping these studies, we identify the common features of permanent campaigning, identifying strong and weak indicators and the extent these are employed by the government, parties, or elected representatives and within which political systems: parliamentarism or presidentialism. Our framework can be applied in future comparative research to understand trends in political communication.